Asuhan keperawatan keluarga dengan masalah personal hygiene pada remaja autisme - Natasha, Cut Windi; Hidayati, Husna; Arnita, Yuni (Indonesian Journal of Health Science, 2024)
Background: Personal hygiene problems are frequently found in autistic children due to their lack of ability to carry out daily functional activities independently, dealing with the situation. The role of the family is absolutely necessary to improve personal hygiene in autistic children. Aim  of  Researc: In this scientific study, it aimed to expound the nursing care of family with personal hygiene problems in autistic adolescents. Research method: This used  descriptive  qualitative  method  with  a  case  study  approach  to  nursing  care,  including  reviewing,  establishing diagnosis, intervening, implementing, and evaluating. Result of Study: Nursing intervention referred to five tasks of family health, including introducing personal hygiene problem, giving support and motivation to the family in taking care of family members related to personal hygiene, demonstrating how to brush teeth and how to wash hands properly, providing a comfortable environment, suggesting family having use the nearby facility. Conclusion: Family nursing care was based on five essential family task in improving interest and family motivation to apply personal hygiene for autistic children. Recommendation: It is also recommended for family members increase family support by always providing positive rewards for the abilities of autistic children. Latar belakang: Masalah Personal hygiene sering dijumpai pada anak autis karena kurangnya kemampuan melakukan aktivitas fungsional sehari-hari secara mandiri. Peran keluarga sangat diperlukan untuk meningkatkan personal hygiene pada anak autis. Tujuan: Karya tulis ilmiah ini bertujuan untuk memberikan gambaran tentang asuhan keperawatan keluarga dengan masalah personal hygiene pada remaja autis. Metode: Penelitian ini menggunakan studi kasus dengan pendekatan asuhan keperawatan keluarga yang meliputi pengkajian, penetapan diagnosa, intervensi, implementasi, dan evaluasi. Hasil: Intervensi keperawatan keluarga yang diberikan merujuk pada lima tugas kesehatan keluarga yaitu pengenalan masalah personal Hygiene, memberikan dukungan dan motivasi pada keluarga untuk merawat anggota keluarga yang mengalami masalah personal Hygiene, demonstrasi cara menggosok gigi dan mencuci tangan dengan baik dan benar, menciptakan lingkungan yang nyaman, serta menganjurkan keluarga untuk memanfaatkan fasilitas kesehatan terdekat. Kesimpulan: Asuhan keperawatan keluarga berdasarkan lima tugas kesehatan keluarga sangat penting dalam meningkatkan minat dan motivasi untuk menerapkan personal hygiene pada anak autis. Saran: Disarankan pada anggota keluarga untuk meningkatkan dukungan keluarga dengan selalu memberikan reward positif atas kemampuan anak dengan autis.